Pengaruh Kepemimpinan Inklusif, Self Efficacy dan Iklim Organisasi Terhadap Perilaku Inovatif Karyawan - Adhelia Putri Salwa; Anak Agung Ketut Diatmika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Rapid developments in science and technology place organizations in the midst of new challenges and unprecedented opportunities. PT. XYZ, a manufacturing company that specializes in chemical coatings or known as